Pengaruh Labelisasi Halal Terhadap Keputusan Pembelian Dengan Religiusitas Sebagai Variabel Intervening Pada Usaha Pempek Di Kota Palembang - Vera Andini (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN - SINTA 4, 2021)
Islam teaches its people to consume halal, holy, and good foods and baverages. Consuming halal, holy and good foods and baverages is obligatory. The halalness of a food and beverage product is manifested in the form of halal certification and a halal sign accompanying a product. One of them is the pempek business in Palembang. This research uses quantitative research, the aim is to determine the influence of halal labeling on purchasing decisions with religiosity as an intervening variable. In this reseacrh, the data were collected by distributing questionnaires to 73 pempek consumers in Palembang using a saturated sample method to determine respondents’ responses to existing variables. The analysis was performed using the method of Structural Equation Modeling (SEM) based on partial least square (PLS). The results of the analysis show that halal labeling affects purchasing decisions in the pempek business in Palembang through religiosity as an intervening variable. It means that halal labeling is able to influence purchasing decisions in the pempek business in Palembang